Ventajas de la medición de niveles plasmáticos de infliximab en pacientes con enfermedad inflamatoria intestinal - Rojas B., René; Covarrubias R., Natalia; Miranda B., Julio; Pérez de Arce O., Edith; Gompertz G., Macarena (Revista Hospital Clínico Universidad de Chile, 2016)
Inflammatory bowel disease includes Crohn ́s disease, ulcerative colitis and unclassifiedcolitis. Conventional therapies used for treating these diseases are often insufficient orcontraindicated and biological agents have proved to be effective and safe in these cases.Infliximab is a quimeric IgG1 monoclonal anti-tumor necrosis factor antibody that is capableof inducing and mantaining clinical remission in patients with inflammatory bowel disease.Despite its proven efficacy a considerable group of patients lose response requiring changesin therapy. Serum Infliximab trough levels are correlated with clinical response, endoscopicremission and mucosal healing in patients with inflammatory bowel disease. Monitoring andadjusting therapy guided by drug serum levels have proved to be more cost-effective and saferthan empiric adjustments. Current international guidelines recommend the measurement ofInfliximab trough levels in the global evaluation and management of these patients to improvetreatment, avoid adverse events and unnecessary costs.